MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA MELALUI REALISTIC MATHEMATIC EDUCATION (RME) - Elita Mega Selvia Wijaya; Nathasa Pramudita Irianti (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
This study aims to improve students' critical thinking skills in the Mathematics Education Major through the Realistic Mathematics Education (RME) Approach. The research method used is Class Action Research according to Kemmis and Mc Taggart which consists of four stages, namely plan, action, observe, and reflect. This research consists of two cycles with each cycle consisting of two meetings. The results showed that the Realistic Mathematics Education (RME) approach can improve students' critical thinking skills. This increase can be seen from the results of student activities that have increased from the first cycle to the second cycle. The increase was apparent from the results of observations of meeting 1 and meeting 2 in the first series of 83.5% and 87.5%, which increased to 86% and 93% in the second cycle. Based on the results of this study it can be concluded that the Realistic Mathematics Education (RME) approach can improve students' critical thinking skills.